2021
DOI: 10.3390/ijerph18189558
|View full text |Cite
|
Sign up to set email alerts
|

ACTonFood. Acceptance and Commitment Therapy-Based Group Treatment Compared to Cognitive Behavioral Therapy-Based Group Treatment for Weight Loss Maintenance: An Individually Randomized Group Treatment Trial

Abstract: The purpose of this Individually Randomized Group Treatment Trial was to compare an Acceptance and Commitment Therapy-based (ACT) group intervention and a Cognitive Behavioral Therapy-based (CBT) group intervention for weight loss maintenance in a sample of adult patients with obesity seeking treatment for weight loss. One hundred and fifty-five adults (BMI: Kg/m2 = 43.8 [6.8]) attending a multidisciplinary rehabilitation program for weight loss were randomized into two conditions: ACT and CBT. Demographical, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
(89 reference statements)
0
9
0
2
Order By: Relevance
“…Despite multidisciplinary interventions have been developed to improve weight loss and to reduce IWS [30][31][32][33][34], the extent to which weight self-stigma affects health outcomes is still unclear [26,27]. To fill the knowledge gaps in the particular field, the Weight Self-Stigma Questionnaire (WSSQ), was shown to be a reliable and valid tool to assess IWS and to detect the impact of effective interventions targeting weight-related stigma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Despite multidisciplinary interventions have been developed to improve weight loss and to reduce IWS [30][31][32][33][34], the extent to which weight self-stigma affects health outcomes is still unclear [26,27]. To fill the knowledge gaps in the particular field, the Weight Self-Stigma Questionnaire (WSSQ), was shown to be a reliable and valid tool to assess IWS and to detect the impact of effective interventions targeting weight-related stigma [17].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence collected in non-clinical samples suggested that psychological inflexibility and experiential avoidance-the unwillingness to remain in contact and consequently, avoid internal states such as unpleasant thoughts, feelings, sensations-played a key role in the relationship between negative emotional states and the onset of emotional eating (Litwin et al, 2017). Among clinical samples the study of the linkage between negative internal states as anxiety and depression, psychological inflexibility, and emotional eating is increasing (Lillis et al, 2011;Niemeier et al, 2012;Schaumberg et al, 2016;Cattivelli et al, 2021;Guerrini Usubini et al, 2021a,b;Di Sante et al, 2022). Within this perspective, the present study was conceived to replicate and extend literature concerning the role of psychological inflexibility on the relationship between negative internal states, and emotional eating in a clinical sample of inpatient adult individuals with obesity seeking for obesity rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions that integrate elements of cognitive behavioural therapy (CBT) have been shown to lead to positive outcomes in improving mental health ( 22 ). In general, most mental health interventions for individuals with obesity aim to increase knowledge about potential difficulties associated with dieting by simultaneously providing psychoeducation about weight biology, increased self-esteem and mental health, improved health and eating behaviours, and physical activity, rather than focusing predominantly on weight loss ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%